Chapter Fishing and territory. Status and perspectives of Sardinia artisanal fisheries. The case of traditional fishery in Asinara Island MPA - Gazale, Vittorio (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This study outlines small-scale fishing Sardinia through specificities related to the state of the fishing fleet at the major and minor port systems of the island, the main techniques, and tools (fixed longlines, bottom trawls, purse seines, casting nets, driftnets). Mapping fishing areas in the Marine Protected Area of Asinara Island was important to define efficient fisheries management measures shared by stakeholders. Therefore, the work focused on the mapping of fishing areas in MPA, its techniques and tools.This work is a premise for future and more applicative lines of research